Relationship between blood cadmium levels and bone mineral density in adults: a cross-sectional study - Lei, Yi; Guo, Meiqian; Xie, Juan; Liu, Xueqing; Li, Xiang; Wang, Hongwu; Xu, Yong; Zheng, Donghui (Frontiers in Endocrinology, 2024)
Introduction ： Osteoporosis, a disease of reduced bone mass and microstructural deterioration leading to fragility fractures, is becoming more prevalent as aging progresses, significantly increasing the socioeconomic burden. In past studies, there has been a growing awareness of the harmful effects of heavy metals on bone, with cadmium being a significant exposure factor. The purpose of this study was to look into the association between adult bone mineral density ( BMD ) and blood cadmium levels.Methods: Based on information from the 2013 -2014, 2017 -2018 NHANES, weighted multiple regression, generalized weighted modeling, and smoothed curve fitting were utilized to investigate the association between blood cadmium and femur BMD. Furthermore, subgroup analyses were conducted to investigate any differences in the associations between age, sex, race, chronic kidney disease, and diabetes.In 2,146 participants, blood cadmium levels and total femur [-0.02 (-0.03, -0.01), 0.0027],femoral neck [-0.01 (-0.02, -0.00), 0.0240], femoral trochanter [-0.01 (-0.02, -0.00), 0.0042], and intertrochanteric femoral trochanter [-0.02 (-0.03, -0.00), 0.0101] BMD were negatively correlated. Subgroup analyses showed that this association was more pronounced in women, non-Hispanic white people and other Hispanics, and those with chronic kidney disease and diabetes. Our results pointed to a negative relationship between femoral BMD and blood cadmium. This negative association varied by age, sex, race, diabetes, and chronic kidney disease. In particular, bone mineral density was more significantly negatively affected by blood cadmium levels in groups with diabetes and chronic kidney disease.